2019
DOI: 10.1590/s1517-707620190001.0654
|View full text |Cite
|
Sign up to set email alerts
|

The devitrification kinetics of transparent silica glass prepared by gel-casting method

Abstract: The kinetics of the crystallization of cristobalite in the amorphous silica glass were studied for samples prepared by gel-casting and sintering in air. Avrami and rate equations were used to calculate the rate constants and the activation energy. The results showed that the crystallization obeys the first order and occurs mainly on the surface with activation energy of 543-546kJ/mol. The fewer amounts of OH-groups and the high amount of oxygen vacancies are expected to stand behind the increase in the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As shown in Figure 1b; and Figure S2, Supporting Information, the white pellet became translucent after CIP (40 MPa, 40 s), and then turned fully transparent and uniform after the UHS process. The UHS method can achieve 1-3 orders of magnitude faster sintering (Figure 1c) compared to other techniques such as gel-casting and sintering, [12] conventional furnace sintering, [10,11,32,33] SPS, [13][14][15][16] laser sintering, [22] and FS. [20] Compared with other sintering methods, our UHS technique has multiple advantages for glass fabrication.…”
Section: Ultrafast Sintering Of Glass In Secondsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 1b; and Figure S2, Supporting Information, the white pellet became translucent after CIP (40 MPa, 40 s), and then turned fully transparent and uniform after the UHS process. The UHS method can achieve 1-3 orders of magnitude faster sintering (Figure 1c) compared to other techniques such as gel-casting and sintering, [12] conventional furnace sintering, [10,11,32,33] SPS, [13][14][15][16] laser sintering, [22] and FS. [20] Compared with other sintering methods, our UHS technique has multiple advantages for glass fabrication.…”
Section: Ultrafast Sintering Of Glass In Secondsmentioning
confidence: 99%
“…Conventional solid‐state sintering can reduce the processing temperature but requires hours‐long thermal treatment to obtain dense silica glasses. [ 10,11 ] It was reported that silica glass with a transmittance of ≈83% could be synthesized by gel‐casting and sintering, in which the sintering temperature was reduced to 1373 K; however, the sintering time was still as long as 3 h. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the glass compositions that can achieve transparent glass components using the sintering method are mostly pure SiO 2 or predominantly composed of SiO 2 . [19][20][21][22][23][24][25][26][27][28][29][30][31][32] This is because silicate glasses usually have high glass transition temperature (T g ), excellent thermal stability, and are less prone to crystallization during sintering. On the other hand, there is limited literature on the preparation of transparent glasses of low T g by sintering method.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, amorphous silica is the best for pozzolanic reaction, formed by the controlled temperature at 600°C-700°C (Hwang and Chandra, 1996). The amorphous silica of well-burnt RHA in single-phase displayed a halo pattern with a peak at around 2θ = 22°by the X-ray diffraction (XRD) test (Chandrasekhar et al, 2003;Al-Hasnawi and Al-Hydary, 2019;Nahar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%